KEBIJAKAN BUMDES DALAM MENSEJAHTERAKAN MASYARAKAT (KASUS PEMBERDAYAAN EKONOMI RAKYAT DI DESA GERSIK PUTIH KECAMATAN GAPURA KABUPATEN SUMENEP) - imam asrori; Slamet Muchsin; Rini Rahayu Kurniati (Ji_Mild (Jurnal Ilmiah Magister Ilmu Administrasi), 2020)
Abstrac:The basis used in this research is Law Number 6 of 2014 concerning Villages which is the beginning of achieving the empowerment of the State and Indonesian Nation from the independence of its villages. This is done by establishing a Village economic institution, namely Village-Owned Enterprises (BUMDES).In this research, the approach used is qualitative with descriptive research type. The research location is in the Village Gersik Putih with the research site at BUMDES Desa Gersik Putih Kec. Gapura Kab. Sumenep. The data sources used are primary data and secondary data. The data collection technique is done by using interview, observation, and documentation techniques. The data analysis technique used consists of data reduction, presentation and verification, which is also called drawing conclusions.The results showed that by empowering the people of Gersik Putih Village, including people who have businesses, the poor, women's business groups, and local residents of Gersik Putih Village, the form of empowerment was by managing various preparations including processed milkfish brains, milkfish brain cakes, fried milkfish. , and roasted / grilled milkfish, BUMDES policies in choosing management have the ability, experience in organizing economic development, and community empowerment, the implementation of policies of the parties involved in implementing policies of all BUMDES administrators, heads, secretaries, treasurers, heads of business units, and workers, the public response in implementing their policies is very good, the obstacles faced by BUMDES in implementing their policies are that some people who have businesses do not want to join BUMDES, the welfare of the community since the existence of BUMDES they have regular income, the needs of the community are all separated nuhi, the economic impact of the village has increased. Keywords: BUMDES Policy, People's Economic Empowerment, Community Welfare.